Trial by market: the Brightstar incubation experiment. (24th August 2010) - Ford, Simon; Probert, David
Established firms accumulate a significant body of knowledge, expertise and capabilities that are often secondary to their central revenue generating activities. How do they leverage this expertise in non-core technology into future value creation opportunities? In this paper we examine an attempt by the telecommunications firm BT to create value from the accumulated knowledge within its laboratories by setting up an incubator. While conceived by the board as a mechanism for leveraging the value of non-core technology into the workplace, corporate support for the incubator was withdrawn after only three years and prompted the incubator to partner with a venture capital firm, NVP, in the spin-out of ventures. Through analysis of this single case we observe how entering into such a relationship reduces the transaction costs of accessing complementary resources, capabilities and competences, while simultaneously reducing a number of the risks associated with venturing for both parties. Partnering with the venture capitalist allows the established firm to get its intellectual property into the market, for it to be tested by the market and further developed.